Green Synthesis and Characterization of Silver Nanoparticles using Mulberry Leaves Extract - Nguyen, Ngoc Thang; Pham, Thi Ngoc; Vu, Tien Hieu; Bui, Van Huan (Old Journal, 2018)
Nowadays, green synthesis of silver nanoparticles (AgNP) had gained so much attention due to increased demand of environmentally friendly technology for material synthesis. In this paper, the silver nanoparticles were synthesized by treating an aqueous silver nitrate solution with Vietnam mulberry leaves extracts, which acted as the reductant and stabilizer silmutaneously. The synthesized silver nanoparticles were characterized by UV-Vis spectroscopy, high-resolution transmission electron microscope (HR-TEM), thermogravimetric analysis (TGA), differential thermal analysis (DTA) and Fourier transform infrared spectroscopy (FT-IR). The observation of the peak at 430 nm in the UV-Vis spectra for the obtained silver nanoparticles reveals the reduction of silver metal ions into silver nanoparticles. The TEM denoted the presence of spherical silver nanoparticles with diameter about 20-35 nm, and the unique size-distribution. The TGA/DTA analysis confirmed the yield of the synthesized silver nanoparticles is 78.22%. The FT-IR analysis was performed to identify the possible functional groups involved in the green synthesis of silver nanoparticles. A possible mechanism was proposed to explain the formation and stabilization of silver nanoparticles.